2014
DOI: 10.3389/fnhum.2014.00628
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between perceptual learning in speech and statistical learning in younger and older adults

Abstract: Within a few sentences, listeners learn to understand severely degraded speech such as noise-vocoded speech. However, individuals vary in the amount of such perceptual learning and it is unclear what underlies these differences. The present study investigates whether perceptual learning in speech relates to statistical learning, as sensitivity to probabilistic information may aid identification of relevant cues in novel speech input. If statistical learning and perceptual learning (partly) draw on the same gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 80 publications
4
53
3
Order By: Relevance
“…This is perhaps unsurprising, as these were the factors that had mixed results in regards to their role in perceptual learning. Our results are in line with the findings of Neger et al (2014), who also found no effect of working memory on perceptual learning in older adults. It is possible that hearing sensitivity still plays a role in the differences we see between our age groups, given that the older adults do have a significantly higher PTA than the younger adults (although both groups are still within the normal range).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is perhaps unsurprising, as these were the factors that had mixed results in regards to their role in perceptual learning. Our results are in line with the findings of Neger et al (2014), who also found no effect of working memory on perceptual learning in older adults. It is possible that hearing sensitivity still plays a role in the differences we see between our age groups, given that the older adults do have a significantly higher PTA than the younger adults (although both groups are still within the normal range).…”
Section: Discussionsupporting
confidence: 83%
“…Lists started at two digits in length and end at eight, with two different lists per length for 16 trials total. Each digit was visually presented for 1000 ms. Digit span was calculated as the proportion of correctly reported sequences (Neger et al, 2014). The digit span task took approximately 5 minutes.…”
Section: Methods Participantsmentioning
confidence: 99%
“…The study by Neger et al (2014) employed a very similar approach and used tests for working memory, processing speed and attention switching control. In contrast to Neger et al (2014), we additionally included tests for the perception of visually degraded speech, lexical abilities and verbal memory as well as a working memory task with distracting information.…”
Section: Discussionmentioning
confidence: 99%
“…Many participants in our study experienced some degree of hearing loss (be it slight), and were, therefore, exposed to a degraded speech signal. Previous research has shown that linguistic experience such as higher vocabulary knowledge facilitates the processing of degraded speech (Janse and Adank, 2012;McAuliffe et al, 2013;Neger et al, 2014) and that this effect is not influenced by word frequency (McAuliffe et al, 2013). In therapy settings, it may thus be beneficial for patients with poorer language proficiency to start with discrimination tasks with simple stimuli (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most older adults listen to a partially degraded auditory signal as they experience agerelated hearing loss. Vocabulary knowledge has been shown to support comprehension of degraded speech such as dysarthric (McAuliffe et al, 2013), noisevocoded (Neger et al, 2014) or accented (Janse and Adank, 2012) speech. Consequently, more cognitive resources might be available to perform the second subtask of stimuli comparison, which is essential for auditory discrimination.…”
Section: Introductionmentioning
confidence: 99%